Psychological Mechanisms of Mathematics Anxiety and Impact on Mathematical Problem-Solving Performance within a Blended Learning Ecosystem Utilizing a Learning Management System (LMS) - Buaddin Hasan; Siska Pratiwi; Enny Listiawati; Nur Aini S; RA. Rica Wijayanti (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This study investigates the psychological mechanisms of mathematics anxiety and its impact on mathematical problem-solving performance within a blended learning ecosystem supported by a Learning Management System (LMS). The primary aim of this research is to examine the relationship between mathematics anxiety and students' mathematical problem-solving abilities in technology-enhanced learning settings. The participants were 60 prospective elementary school teachers enrolled in a mathematics education course that used a blended learning model integrating face-to-face instruction and LMS-based activities. A mixed-methods design was employed to obtain both quantitative and qualitative insights. Quantitative data on mathematics anxiety and problem-solving performance were analyzed using correlational analysis and regression modeling to identify the strength and direction of the relationship between variables. Complementary qualitative data were collected through semi-structured interviews and learning-experience reflections to explore students' cognitive, emotional, and behavioral responses during blended learning, how particularly LMS-mediated tasks shaped their anxiety patterns and strategic approaches to problem solving. Research findings show that the influence of mathematics anxiety on learning performance or problem solving is indirect and influenced by psychological mechanisms and a more complex learning context. Thus, mathematics anxiety cannot be understood separately, but needs to be studied together with other cognitive, affective, and contextual factors.